Nigeria : First Review Under the Policy Support Instrument. (IMF Staff Country Reports; Country Report ;, 2006)
This First Review Under the Policy Support Instrument (PSI) for Nigeria reports that structural reforms are proceeding in line with the National Economic Empowerment and Development Strategy. The authorities' commitments under the PSI primary objectives of the economic reform program include entrenching macroeconomic stability, strengthening public financial management, and reducing the costs of doing business. The Central Bank of Nigeria has developed plans to invest some of its international reserves in higher yield financial assets, and allow domestic banks to bid to be custodians for the investments.